SYNTHESIS OF MOLECULARLY IMPRINTED POLYMERS (MIPS) USED FOR ESTIMATION OF BETAMETHASONE DISODIUM PHOSPHATE (BMSP) USING DIFFERENT FUNCTIONAL MONOMERS - & et al., Al-Abbasi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
Betamethasone sodium phosphate (BMSP)  selective molecularly imprinted polymers(MIPs) were based on ion-pair by prepared four polymers(MIPs) using BMSP as the template a well as (Acryl amide) (AAM), 2-Acrylamido-2-Methyl-1-Propane sulphonic Acid (2-AAMMPSA as monomer, used N,N-ethylenebismethacrylamide (EBMAA) ,ethylene glycol dimethacrylate ethylene glycol(EGDMAC), N, N-methylene bisacrylamide (NNMBAAM)) as cross linker and used benzoyl peroxide as initiator . NIPs prepared by using the same composition of MIPs except the template (BMSP). The MIPs were prepared using variation  ratio of monomer and cross linker .These MIPs applicate as solid phase extraction for determination    BMSP in pharmaceutical preparation used UV as detector .the results gave good response, where the reconstruction percentage (Rec%) value of BMSP drug took the range (99.058149 % - 101.887004 %), and the relative standard deviation (RSD%) value took the range (0.224149 % - 0.743651 %) for standard solution and Rec% took values of (98.400035 - 99.404218) %, and RSD% took values of (0.572589 - 1.012777) % of BMSP drug for the Betamethasone sodium phosphate pharmaceutical.